SUPPLY CHAIN INTEGRATION PERFORMANCE SCALE IN ETHIOPIAN TEXTILE INDUSTRIES - Gamachu, Girma Abdissa; Patrick, Dr. Harold Andrew (The journal of contemporary issues in business and government, 2023)
By combining supply network macro operations and decision-making levels, the study builds an integrated supply chain performance integration measurement scale (SCIPS) framework that offers a more thorough method for investigating supply chain performance measurement. Performance and supply chain-related theories serve as the foundation for the philosophical framework. In addition to looking at performance measures, the study looks into how well the Ethiopian textile industries’ supply chains are integrated. Professionals in the textile sector self-reported the data, and bias analysis was carried out using the standard method. Professionals in the textile sector were mailed or administered the survey, and 385 data points were gathered through the properly filled-out study questionnaire. This study’s objectives included developing an integrated supply chain performance assessment scale for Ethiopia’s textile industries, confirming the factorial design of the measurement, and ultimately identifying the test’s psychometric properties. Exploratory and confirmatory factor analyses were utilized to achieve these objectives. To better grasp the regional realities in this subject, a study was done to comprehend and assess the supply chain in the textile industry, along with any probable causes and practices.